Ceragenins exhibit bactericidal properties that are independent of the ionic strength in the environment mimicking cystic fibrosis sputum - Skłodowski, Karol; Suprewicz, Łukasz; Chmielewska-Deptuła, Sylwia Joanna; Kaliniak, Szczepan; Okła, Sławomir; Zakrzewska, Magdalena; Minarowski, Łukasz; Mróz, Robert; Daniluk, Tamara; Savage, Paul B.; Fiedoruk, Krzysztof; Bucki, Robert (Frontiers in Microbiology, 2023)
The purpose of the work was to investigate the impact of sodium chloride (NaCl) on the antimicrobial efficacy of ceragenins (CSAs) and antimicrobial peptides (AMPs) against bacterial and fungal pathogens associated with cystic fibrosis (CF) lung infections. CF-associated bacterial (Pseudomonas aeruginosa, Ochrobactrum spp., and Staphylococcus aureus), and fungal pathogens (Candida albicans, and Candida tropicalis) were used as target organisms for ceragenins (CSA-13 and CSA-131) and AMPs (LL-37 and omiganan). Susceptibility to the tested compounds was assessed using minimal inhibitory concentrations (MICs) and bactericidal concentrations (MBCs), as well as by colony counting assays in CF sputum samples supplemented with various concentrations of NaCl. Our results demonstrated that ceragenins exhibit potent antimicrobial activity in CF sputum regardless of the NaCl concentration when compared to LL-37 and omiganan. Given the broad-spectrum antimicrobial activity of ceragenins in the microenvironments mimicking the airways of CF patients, ceragenins might be promising agents in managing CF disease.